Indole/oxazolone functionalized coumarins as pH-sensitive fluorescent kinase inhibitors. (6th July 2022) - Shamsiya, Aranhikkal; Pathoor, Rajeena; Bahulayan, D.
Graphical abstract: Highlights: Simple and green strategy for the construction of pH-sensitive fluorescent kinase inhibitors. Efficient use of scaffolding approach for smart property generation. Harvesting of dual properties like the potential for both imaging and therapy. Selective targeting of CDK2. Abstract: A simple MCR-Click strategy for the construction of pH-sensitive fluorescent kinase inhibitors by scaffolding a coumarin core with an indole or oxazolone moiety is described. The fluorescent probes thus obtained showed click on fluorescence useful for imaging pH-sensitive tumors, and inhibitor properties against cancer causing cyclin dependent kinase, CDK2. The optical and biological properties observed were rationalized based on DFT calculations and bioassays. The selective binding of these probes with CDK2 and their cytotoxicity towards HeLa cells without affecting normal cells demonstrates that the methodology described here is potentially useful for the design of dual functional probe cum inhibitors for imaging and therapy.